Factors Related with Waste Segregation at the Nagari Tigo Jangko Traditional Market - Yulianto, Beny; Syukrina, Afifa Dwi; Wahyuni, Denai (Alifah Health Science Symposium Proceeding, 2023)
Garbage is the solid residue of our daily activities and natural processes. Garbage has become a worldwide and Indonesian issue. Households generate the most garbage, followed by conventional markets. Food/vegetable trash accounts for 52% of Tanah Datar District waste, followed by plastic (17%) and paper/cardboard (13%). Nagari Tigo Jangko Traditional Market generates approximately 128,987 tons of garbage every year, with a total of 10,695 tons per month and 6,874 kg per day, with an average of 370.92 tons transported. The purpose of this research is to investigate the factors influencing garbage segregation at Nagari Tigo Jangko Traditional Market. This is a quantitative study using a cross-sectional design. The study was conducted during April until May of 2023. The research sample was all traders at Nagari Tigo Jangko Traditional Market, totaling 115 traders, the sampling technique used Total Sampling. Data analysis was performed univariate and bivariate with the Chi-Square test (α = 0.05). The results of the bivariate analysis showed that there was no relationship between knowledge (P = 0.121 > α = 0.05), education (P = 0.196 > α = 0.05) and those related to action (P = 0.00 <α = 0.05), facilities and infrastructure (P = 0.00 < α = 0.05) with waste segregation. It is suggested to the market to provide facilities and infrastructure such as trash bins which are divided into 2 types in each stall, as well as to impose sanctions on traders who litter.